2015
DOI: 10.1107/s1600577514025880
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the iron oxidation state and coordination geometry in iron oxide- and zeolite-based catalysts using pre-edge XAS analysis

Abstract: Analysis of the oxidation state and coordination geometry using pre-edge analysis is attractive for heterogeneous catalysis and materials science, especially for in situ and time-resolved studies or highly diluted systems. In the present study, focus is laid on iron-based catalysts. First a systematic investigation of the pre-edge region of the Fe K-edge using staurolite, FePO4, FeO and α-Fe2O3 as reference compounds for tetrahedral Fe(2+), tetrahedral Fe(3+), octahedral Fe(2+) and octahedral Fe(3+), respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
76
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 61 publications
10
76
0
2
Order By: Relevance
“…(b) Centroid position of the pre‐edge peak as a function of the shock pressure (black symbols) and the subsequent heating (red symbols). (c) Calibration curve (from Boubnov et al, ) shows a linear relationship between the centroid position of the preedge peak for hematite (Fe 3+ /Total Fe = 1), magnetite (Fe 3+ /Total Fe = 0.67) and synthetic fayalite, Fe 2 SiO 4 (Fe 3+ /Total Fe = 0). Blue arrows indicate position of reference oxides according to Bajt et al () while the blue frame shows data of this study shown in Figure 7b.…”
Section: Resultsmentioning
confidence: 99%
“…(b) Centroid position of the pre‐edge peak as a function of the shock pressure (black symbols) and the subsequent heating (red symbols). (c) Calibration curve (from Boubnov et al, ) shows a linear relationship between the centroid position of the preedge peak for hematite (Fe 3+ /Total Fe = 1), magnetite (Fe 3+ /Total Fe = 0.67) and synthetic fayalite, Fe 2 SiO 4 (Fe 3+ /Total Fe = 0). Blue arrows indicate position of reference oxides according to Bajt et al () while the blue frame shows data of this study shown in Figure 7b.…”
Section: Resultsmentioning
confidence: 99%
“…The spectra were merged and normalised. Pre-edge spectra were extracted from the near-edge structure (XANES) spectra by using an arctangent function and a first-degree polynomial, modelling the onset of the absorption edge [39]. The extracted pre-edge peak was modelled by a variable number of pseudo-Voigt peak functions, allowing the FWHM to float at around 2-3 eV.…”
Section: X-ray Absorption Spectroscopymentioning
confidence: 99%
“…XANES spectra were collected in situ at high pressure and temperature by coupling a DAC and a double-sided laser heating setup. Extended description of the experimental methods and spectrum analysis can be found in the supporting information (Akahama & Kawamura, 2004;Benedetti & Loubeyre, 2004;Boccato et al, 2017;Boubnov et al, 2015;Dewaele et al, 2008;Dräger et al, 1988;Galoisy et al, 2001;Giampaoli et al, 2018;Waychunas et al, 1983;Max Wilke et al, 2005). Due to the X-ray absorption setup used, no simultaneous X-ray diffraction could be performed; we thus assume the phases present from previous X-ray diffraction measurements on the same assemblages and at the same pressure and temperature conditions (e.g., Bykova et al, 2016;Fischer et al, 2011;Hu et al, 2016).…”
Section: Methodsmentioning
confidence: 99%